2009
DOI: 10.2319/042108-223.1
|View full text |Cite
|
Sign up to set email alerts
|

Chromium Release from New Stainless Steel, Recycled and Nickel-free Orthodontic Brackets

Abstract: The hypothesis is rejected, but the amount of chromium released in all test solutions was well below the daily dietary intake level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 19 publications
6
39
0
1
Order By: Relevance
“…25,26 In their in vitro research, Sfondrini et al proved that the highest amount of chromium is released from new steel brackets (0.52-1.083 μg/g), but less from recycled brackets (0.27-0.38 μg/g). 27 Some symptoms of allergy to nickel may appear in the oral cavity in patients treated with fixed orthodontic appliances. The symptoms include inflammation of gums and tongue, gingival hypertrophy, erythema multiforme, exfoliation of the lip epithelium and metallic aftertaste in the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In their in vitro research, Sfondrini et al proved that the highest amount of chromium is released from new steel brackets (0.52-1.083 μg/g), but less from recycled brackets (0.27-0.38 μg/g). 27 Some symptoms of allergy to nickel may appear in the oral cavity in patients treated with fixed orthodontic appliances. The symptoms include inflammation of gums and tongue, gingival hypertrophy, erythema multiforme, exfoliation of the lip epithelium and metallic aftertaste in the mouth.…”
Section: Discussionmentioning
confidence: 99%
“…Chromium release has been assessed both in vitro and in vivo. Sfondrini et al [1] found that chromium is released in higher quantities from new stainless steel brackets than from recycled ones and that release increased at ph 4.2 in their in vitro investigation. Matos de Souza and Macedo de Menezes [61] found that chromium and nickel ion concentrations increased ten minutes after placement of orthodontic appliances in the mouth in their in vivo investigation.…”
Section: Corrosion and Elemental Releasementioning
confidence: 99%
“…Stainless steel has many uses in orthodontics for the fabrication of brackets, archwires, bands, ligatures, among other appliances [1]. Stainless steel is an alloy composed of iron and carbon that contains chromium, nickel, and other elements that impart the property of resisting corrosion [2].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc and copper are released from stainless steel due to the electronic structure of such elements at the atomic level and the phase structure of the alloy [30]. Chromium is also released by this alloy [14,34]. Nickel, a known allergen, is released by nickel-titanium and stainless steel orthodontic alloys [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the chemical composition of commercially pure titanium and Ti6Al4V alloy. Stainless steel is an alloy that is commonly used in orthodontics for manufacturing brackets, wires, ligatures, bands, and other applications [3,14]. This alloy is composed of iron and carbon and contains smaller quantities of nickel, chromium, and other elements that impart the property of resisting corrosion [15].…”
Section: Introductionmentioning
confidence: 99%